The Determination of the Principal’s Leadership Style, Teachers’ Work Motivation, and Mind-set of the Performance of Elementary School Teachers: Indonesia - Yasa, I Putu Grantika; Widana, I Wayan; Aisyah, Siti (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2023)
This research aimed to find out and analyze the partial determination of leadership style, work motivation, and mindset on teachers’ performance and to know the simultaneous influence of leadership style determination, teachers’ work motivation, and mindset on the performance of elementary school teachers in Marga District. The population was all 320 elementary school teachers in Marga District. For the total sample taken, the researchers used the Slovin technique to obtain 76 teachers using a simple multi-stage random sampling technique. The data collection technique in this research is a questionnaire. In analyzing the research data, the researcher used linear regression analysis and multiple linear regression with the help of the SPSS program. From the research results, the principal's leadership style variable has a significant effect on the performance of elementary school teachers in the Marga District with a sig value of 0.000 <0.05. The teachers’ work motivation variable also has a significant effect on the performance of elementary school teachers in Marga District with a value of sig. = 0.001 <0.05. The principal's leadership style variable also has a significant effect on the performance of elementary school teachers in Marga District with a sig value of 0.000 <0.05. Simultaneously, the three independent variables have a relationship with the dependent variable, namely the performance of elementary school teachers in Marga District, as indicated by a coefficient of determination (R-Square) of 0.650. It means that simultaneously, the magnitude of the coefficient of determination (R-Square) of 0.650 has an effect of 65% on the performance of elementary school teachers.